Querying Patients With Cancer About Sexual Health and Sexual and Gender Minority Status: A Qualitative Study of Health-Care Providers. (June 2020) - Cathcart-Rake, Elizabeth; O'Connor, Jennifer M.; Ridgeway, Jennifer L.; Breitkopf, Carmen Radecki; Guire, Lois J. Mc; Olson, Eric A.; Kaur, Judith S.; Leventakos, Konstantinos; Jatoi, Aminah
Background: Although national organizations advocate that health-care providers ask patients about sexual health and sexual and gender minority status—to learn, for example, about side effects of treatment and to understand patients' social support—these conversations often do not occur. This study explored health-care providers' reasons for having/not having these conversations. Methods: This single-institution study recruited health-care providers from medical oncology, hematology, radiation oncology, and gynecology. Face-to-face interviews were recorded, transcribed, and analyzed qualitatively. Results: Three main themes emerged: (1) patient-centric reasons for discussing/not discussing sexual health and sexual and gender minority status ("So I think just the holistic viewpoint is important"); (2) health-care provider–centric reasons for discussing/not discussing these issues ("That's going to take more time to talk about and to deal with…" or "I was raised orthodox, so this is not something we talk about…"; and (3) reasons that appeared to straddle both of the above themes (eg, acknowledgment of the sometimes taboo nature of these topics). Conclusion: Although many health-care providers favor talking with patients with cancer about sexual health and sexual and gender minority status, limited time, personal reluctance, and the taboo nature of these topics appear at times to hamper the initiation of these conversations.